Exploiting Klebsiella pneumoniae genomics for its significance in One Health - Wang, Jiayu (The University of Edinburgh, 2025)
This thesis explores the genomics and epidemiological dynamics of Klebsiella variicola (K. var) and Klebsiella pneumoniae (K. pne), focusing on their adaptation to human hosts, resistance profiles, and virulence traits. We begin by investigating the population structure and niche adaptation of K. var through a comprehensive genomic dataset. Our analysis reveals how this pathogen, traditionally associated with plants, has transitioned into the human niche through the acquisition of genes either due to antibiotic overuse or proximity to K. pne, highlighting its genetic variability and potential public health threat. To understand its behaviour in clinical infections, we conducted a case study in Scotland involving 119 clinical strains collected in 2023. This study identified multidrug-resistant and virulent strains carrying the yersiniabactin gene, underscoring the resistance and virulence of K. var in Scotland and emphasizing the need for ongoing surveillance. We next shifted our focus to K. pne, a close relative of K. var, examining epidemic clones such as ST11, ST15, and ST258. We analysed their global dissemination and resistance/virulence profiles, with particular attention to ST11, which has caused significant outbreaks in China. Our genomic analysis revealed distinct evolutionary paths within the ST11 lineage, particularly in the Asian cluster, where resistance to extended-spectrum-β-lactams and virulence traits, such as aerobactin and yersiniabactin, were prevalent. Furthermore, we identified key resistance mechanisms linked to fluoroquinolone and colistin resistance, particularly in a hypervirulent clonal expansion cluster of ST11. Overall, this thesis advances the understanding of how these Klebsiella species evolve, adapt, and contribute to significant public health challenges due to their resistance and virulence traits. These findings underscore the need for continued surveillance and control measures to mitigate the risks posed by these emerging pathogens under a One Health framework.
Keywords: Klebsiella; Evolution; Adaptation; Resistance; Virulence